PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TURNAMENT BERBANTUAN MEDIA QUIZALIZE TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS V DI SDN RAMBUTAN 03 PAGI - Najwa Apriliani Azahra; Khavisa Pranata (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was motivated by the low learning motivation of students in the subject of Pancasila Education, particularly in fifth grade at SDN Rambutan 03 Pagi. The use of conventional teaching methods has led to passive student engagement and boredom. This study aims to examine the effect of implementing the Teams Games Tournament (TGT) learning model assisted by the Quizalize digital platform on students’ learning motivation. A quantitative method with a quasi-experimental design using a one-group pretest-posttest was employed. Data were collected through a learning motivation questionnaire and analyzed using a paired sample t-test with the aid of SPSS. The results revealed a significant increase in students’ learning motivation after applying the TGT model with Quizalize, as evidenced by a significance value (sig. 2-tailed) of 0.001 < 0.05. These findings indicate that combining cooperative, game-based learning with interactive technology fosters a more engaging and enjoyable learning environment. Therefore, the TGT model supported by Quizalize has proven effective in enhancing student motivation and can serve as an innovative learning strategy, especially for Pancasila Education at the elementary level.